2015
DOI: 10.1007/s00424-015-1693-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of the epithelial sodium channel δ-subunit in human respiratory epithelial cells in vitro

Abstract: CitationExpression and function of the epithelial sodium channelsubunit in human respiratory epithelial cells in vitro. ABSTRACTUsing human airway epithelial cell lines (i.e. NCI-H441 and Calu-3) as well as human alveolar epithelial type I-like (ATI) cells in primary culture, we studied the contribution of the epithelial sodium channel δ-subunit (δ-ENaC) to transepithelial sodium transport in human lung in vitro. Endogenous δ-ENaC protein was present in all three cell types tested, however, protein abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The analysis was not carried out in freshly isolated AT2 cells due to their unpolarized phenotype. Apical or basolateral membrane proteins of confluent, Transwell-grown cell monolayers were labeled with sulpho-NHS-biotin (Thermo Fisher Scientific), isolated and analyzed as described in a previously published protocol ( Schwagerus et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was not carried out in freshly isolated AT2 cells due to their unpolarized phenotype. Apical or basolateral membrane proteins of confluent, Transwell-grown cell monolayers were labeled with sulpho-NHS-biotin (Thermo Fisher Scientific), isolated and analyzed as described in a previously published protocol ( Schwagerus et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…In subsequent studies, capsazepine was shown to activate currents in ENaCδ1βγ‐ and ENaCδ2βγ‐expressing oocytes with EC 50 values of 6.3 and 11.9 µM, respectively 83 . In another study, capsazepine activated Na + currents in NCI‐H441 cells overexpressing ENaCδ but inhibited these currents in wild‐type cells 84 . However, high concentrations of capsazepine (250 µM) have been reported to inhibit currents in Xenopus oocytes expressing the rat ENaCαβγ channel 85 .…”
Section: Effects Of Capsaicinoids On Voltage‐gated Sodium Channelsmentioning
confidence: 96%
“…83 In another study, capsazepine activated Na + currents in NCI-H441 cells overexpressing ENaCδ but inhibited these currents in wild-type cells. 84 However, high concentrations of capsazepine (250 µM) have been reported to inhibit currents in Xenopus oocytes expressing the rat ENaCαβγ channel. 85 In summary, these results indicate that while capsaicin inhibits VGSCs, capsazepine inhibits ENaCs in a TRPV1-independent manner.…”
Section: Effects Of Capsaicinoids On Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…Cell surface proteins were labelled with biotin, isolated and analysed according to a previously published protocol (34). Briefly, Transwell-grown cell monolayers were washed with ice-cold PBS and incubated for 20 min at 4°C with Pierce sulfo-NHS-biotin (Thermo Nuclear and cytoplasmic protein concentrations were determined by Pierce BCA protein assay kit and equal amounts of proteins were used for immunoblotting as described above.…”
Section: Biotinylation Of Cell Surface Proteinsmentioning
confidence: 99%